Peningkatan Keterampilan Guru Dalam Pembuatan Media Pembelajaran Berbasis Canva Melalui Kegiatan In House Training: Di SD Negeri 1 Babaktulung Semester 1 Tahun Pelajaran 2021/2022 - Supriyanto, Supriyanto (Universitas Cokroaminoto Yogyakarta, 2022)
School Action Research aims to improve teacher skills in making Canva-based learning media by implementing iHT activities. The type of research is School Action Research. The research subjects were 12 teachers. Data collection techniques using observation and documentation techniques. Data validation with triangulation technique. The data analysis method used qualitative data analysis. The increase in the results of the assessment of the skills of teachers at SDN 1 Babaktulung in making Canva-based learning media in the initial conditions an average value of 44.68 in the Less (K) category, increased in the first cycle with an average value of 69.54 and in the Enough category. (C) and in the second cycle the average score was 89.66 in the Good category (B). The improvement of the skills of teachers at SDN 1 Babaktulung in making individual Canva-based learning media in the initial conditions there were no teachers declared complete, in the first cycle 6 teachers or 50% were declared complete and in the second cycle 12 teachers or 100% were declared complete.